Knowledge, attitude and practice toward anemia among mothers of adolescent girls in Puducherry, South India: a community-based cross-sectional study - Ramachandran, Rajeswari; Subash, Jeyagowri; Harikrishnan, Jeevaharini; Nagappan, Narmatha; Pazhanisamy, Sowmiya (International Journal Of Community Medicine And Public Health, 2026)
Background: Anemia remains a major public health problem among adolescent girls in India, with adverse effects on growth, cognitive development, and future maternal health. Mothers play a key role in influencing adolescents’ dietary and health behaviors. This study assessed the knowledge, attitude, and practice (KAP) regarding anemia among mothers of adolescent girls in Puducherry and examined their association with selected demographic variables. Methods: A community-based descriptive cross-sectional study was conducted among 160 mothers of adolescent girls selected through convenience sampling. Data were collected using a structured knowledge questionnaire, attitude scale, and practice checklist. Descriptive statistics and Chi-square tests were used for data analysis. A p value <0.05 was considered statistically significant. Results: Adequate knowledge regarding anemia was observed in 42.5% of mothers, while 38.8% had moderate knowledge. Most mothers (83.8%) demonstrated a positive attitude toward anemia prevention. Moderate preventive practices were reported by 68.8% of mothers, and 25.0% exhibited good practices. The mean±SD scores for knowledge, attitude, and practice were 12.22±4.60, 36.02±6.90, and 6.22±1.71, respectively. Maternal age was significantly associated with knowledge (p=0.014) and practice (p=0.010). Educational level was significantly associated with knowledge and practice (p<0.001). Monthly family income (p=0.016) and place of residence (p=0.036) were also significantly associated with practice. Conclusions: Despite positive attitudes, gaps in maternal knowledge and preventive practices persist. Targeted educational interventions focusing on socio-demographic determinants may strengthen anemia prevention among adolescent girls.